PTH-177 Radiofrequency ablation for complicated barrett's oesophagus: experience of a tertiary centre in northern ireland at 5 years. (22nd June 2015) - Hall, P; Reed, O; Mainie, I
Abstract : Introduction: The 2013 British Society of Gastroenterology (BSG) guideline supports first line use of endoscopic therapy in patients with dysplastic Barrett's oesophagus or intramucosal carcinoma (IMC). 1 Endoscopic mucosal resection (EMR) and radiofrequency ablation (RFA) can be used instead of oesophagectomy in fit patients and allows treatment of those unfit for surgery. We aimed to evaluate the outcomes of our centre's RFA programme after 5 years, in a tertiary referral centre for Northern Ireland. Method: A patient database was compiled by searching a hospital's endoscopy reporting system for 'radiofrequency', 'RFA', and 'HALO'. We retrospectively gathered histology and follow up data using patient letters and laboratory records. Results: 45 patients (39M:6F) mean age 67, received RFA for low/high grade dysplasia (LGD, HGD) or IMC. Prior histology demonstrated 3 LGD, 29 HGD and 13 IMC. Average Prague score: C4.4 M5.6. Of these patients who received RFA, 82% (37/45) had required endoscopic mucosal resection (EMR) of visible lesions prior to therapy. A mean of 1.82 sessions of EMR were needed (range 0–7). 77 sessions of RFA were received by the 45 patients (mean 1.71 sessions). 36 patients were treated by the end of 2013 with only 7 of these (19.4%) referred for surgery by the end of 2014. The remaining 80.6% showed either complete eradication of Barrett's (58%), eradication of dysplasia (17%) or are awaiting further endoscopic therapy with view to eradication of dysplasia (6%). There were no deaths related to endoscopic treatment and no major complications. 2 patients needed stricture dilatation and several had minor bleeding. Those referred for oesophagectomy from the programme fell from 4 in 2011 to only 1 over the last 2 years. This could represent increased confidence in EMR/RFA from the multidisciplinary team (MDT) with time. Of the initial 7 patients referred by the MDT for oesophagectomy only 1 specimen showed carcinoma with submucosal involvement. The remaining specimens showed 2 with IMC (29%), 1 with HGD (14%) and 3 (43%) with Barrett's metaplasia alone. Conclusion: Endoscopic therapy is safe and effective in treating complicated Barrett's. Most patients (82%) will require EMR prior to RFA and this should be incorporated into planned treatment schedules. Our figures show an overall surgery rate of 19% which is falling with time as multidisciplinary confidence with endoscopic therapy improves. We anticipate service expansion, particularly with recent evidence showing benefits in the ablation of LGD. 2 Disclosure of interest: None Declared. References: Fitzgerald RC, et al . Guidelines on the diagnosis and management of Barrett's oesophagus. BSG 2013 Phoa KN, et al . Radiofrequency ablation vs endoscopic surveillance for patients with Barrett esophagus and low-grade dysplasia. JAMA 2014;311(12):1209–1217